NSDI Initiatives in Nepal : An Overview - Bhatta, Ganesh Prasad (Journal on Geoinformatics, Nepal, 2007)
Geospatial data, information and technologies are becoming more important and more common tools throughout the world because of their capacity to improve government and private sector decision making. Geospatial information is developed, used, maintained and shared in a various range of application areas. Sharing geospatial data in various applications helps to improve the management of public infrastructure and natural resources and further, it minimizes the duplication of resources invested in producing geospatial data. Many nations around the world are developing National Spatial Data Infrastructures (NSDI) to help facilitating cooperative production, use and sharing of geospatial information. In Nepal, NSDI initiatives have been taken through the National Geographic Information Infrastructure Program (NGIIP) under Survey Department, the National Mapping Organisation (NMO) of Nepal, since 2002. Due to various reasons, the NSDI initiatives in Nepal have not come to full functional stage yet. Various issues related to the development of full functional NSDI in the country are to be taken into consideration. This paper tries to give an overview of the state-of-the-art of the initiatives to suggest better way out for full functional NSDI in Nepal.